2024
DOI: 10.1109/tem.2022.3144741
|View full text |Cite
|
Sign up to set email alerts
|

Value Leakage in Product–Service System Provision: A Business Model Alignment Perspective

Abstract: To stay competitive, manufacturing companies offer product-service systems (PSS) to avoid commoditization of their products. The potential to create value through PSS offerings lies in a company's ability to successfully implement the PSS business model. However, many companies are unable to realize the benefits because PSS represents significant changes to all the business model elements, which comprise value creation, value delivery, and value capture. This leads to misalignment among the business model elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…However, empirical studies on the development of such new relationships with and among stakeholders point to several difficulties. For instance, Reim et al (2022) empirically identified several alignment problems as a consequence of interactions between different elements of sustainable business models. Other empirical studies have pointed to the need for better collaboration with stakeholders involving broader product ecosystems (Barreiro‐Gen & Lozano, 2020; Diaz et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, empirical studies on the development of such new relationships with and among stakeholders point to several difficulties. For instance, Reim et al (2022) empirically identified several alignment problems as a consequence of interactions between different elements of sustainable business models. Other empirical studies have pointed to the need for better collaboration with stakeholders involving broader product ecosystems (Barreiro‐Gen & Lozano, 2020; Diaz et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Business model as a concept is a recent addition to developmental management research. A common argument in the literature states that business model refers to the logic of the company, including how it operates and how it creates value for stakeholders (Reim, 2018). Over the last few years, more and more agreement has arisen for a common definition, as used by Teece (2010) and Osterwalder and Pigneur (2010), which basically states that business models describe the design or architecture of the value creation, value delivery and value capturing mechanisms that a company employs.…”
Section: Introductionmentioning
confidence: 99%